2013
DOI: 10.1128/cvi.00615-12
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Membrane Proximal External Region Lipopeptides Containing Chemical Modifications for HIV-1 Vaccination

Abstract: The inability to generate broadly neutralizing antibody (bnAb) responses to the membrane proximal external region (MPER) of HIV-1 gp41 using current vaccine strategies has hampered efforts to prevent the spread of HIV. To address this challenge, we investigated a novel hypothesis to help improve the anti-MPER antibody response. Guided by structural insights and the unique lipid reactivity of anti-MPER bnAbs, we considered whether amino acid side chain modifications that emulate hydrophilic phospholipid head gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 64 publications
0
14
1
Order By: Relevance
“…However, monoclonal antibodies against the MPER have been shown to exert similar protective effects than anti-gp120 antibodies in non human primate models [5]. Therefore the elicitation of neutralizing anti-MPER responses by several candidate immunogens is still a major issue in HIV vaccine research, although it has been unsuccessful to date [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…However, monoclonal antibodies against the MPER have been shown to exert similar protective effects than anti-gp120 antibodies in non human primate models [5]. Therefore the elicitation of neutralizing anti-MPER responses by several candidate immunogens is still a major issue in HIV vaccine research, although it has been unsuccessful to date [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Reciprocal endpoint titers of antisera were determined by enzyme-linked immunosorbent assays (ELISA) as previously described (21). The titer was defined as the reciprocal dilution of antisera yielding an optical density twice that of the background.…”
Section: Methodsmentioning
confidence: 99%
“…This hypothesis stems from the ubiquitous nature of posttranslational modifications during the inflammatory immune response (22), the fact that posttranslational modification mimetics have been shown to break tolerance in model systems (23,24), and the altered binding of posttranslationally modified peptides in the major histocompatibility complex (MHC), with the subsequent induction of T cell responses (25). In our earlier study (21), we showed that partial MPER immunogens bearing chemically modified side chains can induce high anti-MPER antibody titers in rabbits. Although we failed to elicit neutralizing antibodies, we confirmed that these modifications do not alter the affinities of bNAbs 2F5 and 4E10 toward their cognate epitopes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of employing the intact Env antigen protein, some groups have employed short epitope peptides on liposomes [59][60][61][62][63][64][65][66]. The MPER, a functional domain of Env gp41, is highly conserved and is a target epitope of several bNAbs, such as 4E10 and 10E8 [10].…”
Section: Synthetic Nanoparticles For Presentation Of Hiv-1 Antigensmentioning
confidence: 99%